Stimulation of orexin/hypocretin neurones by thyrotropin-releasing hormone. - González, J; Horjales-Araujo, E; Fugger, L; Broberger, C; Burdakov, D (2009)
Central orexin/hypocretin neurones are critical for sustaining consciousness: their firing stimulates wakefulness and their destruction causes narcolepsy. We explored whether the activity of orexin cells is modulated by thyrotropin-releasing hormone (TRH), an endogenous stimulant of wakefulness and locomotor activity whose mechanism of action is not fully understood. Living orexin neurones were identified by targeted expression of green fluorescent protein (GFP) in acute brain slices of transgenic mice. Using whole-cell patch-clamp recordings, we found that TRH robustly increased the action potential firing rate of these neurones. TRH-induced excitation persisted under conditions of synaptic isolation, and involved a Na(+)-dependent depolarization and activation of a mixed cation current in the orexin cell membrane. By double-label immunohistochemistry, we found close appositions between TRH-immunoreactive nerve terminals and orexin-A-immunoreactive cell bodies. These results identify a new physiological modulator of orexin cell firing, and suggest that orexin cell excitation may contribute to the arousal-enhancing actions of TRH.